9 Enhancing community health outcomes (project ECHO): developing a community of practice for paramedics in end of life care (EOLC). Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - McTague, Laura; Hodge, Andrew; Williams, Clare; Taylor, Paul; Kyeremateng, Sam
Abstract : Background: Paramedics report unique challenges when delivering EOLC, including accessing education and having low confidence. Yorkshire Ambulance Service (YAS) covers a large geographical area and education is typically centralised. Project ECHO uses a tele-mentoring network to share best practice, enable case-based learning to manage complexity, develop communities of practice and build capacity in logistically and geographically challenged services. Prior implementations demonstrated improved knowledge, confidence and self-efficacy in participants. We piloted the ECHO model to develop EOLC amongst YAS clinicians. Method: This project began in October 2018 and is planned to run until March 2019; it recruited to capacity (30 participants) within a day. Participants joined a virtual knowledge event to shape the curriculum. Five ECHO sessions, occurring monthly, were facilitated by a Consultant Palliative Physician and a Consultant Paramedic. Participants from across Yorkshire 'dialled in' remotely, individually or in groups. Each session comprised an expert didactic and two anonymised case presentations from participants, which formed the basis of facilitated discussions. Session resources were emailed. Electronic surveys based on existing research were completed by participants: a knowledge questionnaire on recruitment; self-completed surveys of knowledge and self-efficacy at the start and after 3 sessions, and individual session evaluations. Results: Of the 30 applicants, 27, 23 and 28 attended each of the first 3 sessions. Of these, 18 completed the initial survey and 16 the second. The proportion of participants self-reporting as 'competent' or 'very competent' increased in 4 out of 5 domains related to EOLC. The proportion reporting 'agree' or 'strongly agree' with questions related to competence in EOLC increased in 12 out of 16 domains. Conclusions: Attendance and recruitment rates indicate that ECHO is an accessible model of education delivery. The survey findings support the successful application of this model to paramedics delivering EOLC, resulting in improved self-reported knowledge and confidence.